ANALISIS WAKTU TIDUR TERHADAP PENGARUH INDEKS PRESTASI MAHASISWA KELAS PSM 2020 A MENGGUNAKAN UJI MANN WHITNEY - Tarigan, Dandi Rifa'i; Panggabean, Natanael; Manullang, Sudianto; Nadia Amalia, Sisti (NUMBERS : Jurnal Pendidikan Matematika & Ilmu Pengetahuan Alam, 2024)
This study aims to analyze the influence of sleep duration on students' academic performance using the Mann-Whitney U test. Sufficient sleep duration plays a vital role in maintaining one's health and academic achievement. The data was collected from a sample of PSM class of 2020 at a state university of medan. The data was divided into two groups based on sleep duration: a group with less than 7 hours of sleep and a group with 7 hours or more of sleep. The Mann-Whitney U test was employed to compare the total ranks of the two groups in the dataset. The results of the study revealed a correlation between sleep duration and students' academic performance. If the calculated U value is lower than the critical U value at the determined significance level, the null hypothesis is rejected, indicating a significant difference in academic performance between the two sleep duration groups. This study provides insights into the importance of maintaining sufficient sleep duration to support students' academic achievement. It is hoped that this research can serve as a reference for improving sleep quality and academic performance among students.